Perancangan Sistem Pendukung Keputusan Penentuan Jurusan Siswa Sma Negeri 2 Kutacane Berbasis Web Dengan Menggunakan Metode Analytical Hierarchy Process (AHP) - Ariani Susanti (Cattleya Darmaya Fortuna, 2021)
The world of education is currently also growing rapidly, with many schools that offer various majors, each of which has its advantages, so that people are also free to choose according to their interests. This makes schools must also have a good system to be able to direct the community to choices according to their abilities. A decision support system (Desicion Support System) can help provide various alternatives that can be taken in the decision-making process. There are many methods that can be used by decision makers to help find the optimal solution or alternative for a problem.The Decision Support System for Determining Majors serves to help schools make the right decisions using the Analytical Hierarchy Process method. The main function of this software is to process data on the selection of high school students majors. This software is implemented using the web, and for the database using Mysql.